Legal Aspects of Receiving Transplants from a Living Donor - YELUBAYEV, Abzal B.; BAISSEITOVA, Aliya T. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The article is concerned with the legal aspects of receiving a transplant from a living donor as the object of criminal and legal research. The authors study conditions for the legality of receiving a transplant from a living donor. While considering the Kazakh legislation and the experience of other countries in this area, the authors have also developed specific recommendations and methods for studying legal aspects of receiving a transplant from a living donor in Kazakhstan and foreign countries. The authors have determined the social danger of this criminal offense: citizens of Kazakhstan do not sufficiently value their health, which can lead to criminal consequences where the object is human life and health. The subject is any organs or tissues. According to the study results, legal aspects of receiving a transplant from a living donor largely depends on the theoretical elaboration of the problem under consideration, which will further improve the current Criminal Law and develop effective measures to counter the criminal offense in question.